THE VIBRANT TAPESTRY OF PUNJAB: EXPLORING THE RICH TRADITION OF ARTS AND CRAFTS - Jyoti; Rani, Neetu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The vibrant state of Punjab, a land synonymous with cultural opulence and artistic diversity, offers a unique tapestry of arts and crafts that encapsulates the essence of its rich heritage and communal ethos. This paper embarks on an explorative journey into the heart of Punjab’s traditional crafts, unveiling the myriad ways in which these art forms serve as a conduit for cultural expression, economic sustenance, and preservation of heritage. Each craft, be it the intricate basketry, the colorful durries, the traditional folk toys, the elegant juttis, the distinctive mud works, the evocative Punjabi paintings, the exquisite Phulkari, the meticulous weaving, the masterful woodwork, the enduring leather craft, or the resplendent metalwork, narrates a story of timeless tradition, meticulous skill, and a deep-seated reverence for artistry. These crafts are not mere artifacts; they are vibrant testimonies to Punjab’s enduring legacy, reflecting the creativity, resilience, and the indomitable spirit of its people. By delving into the depths of these traditional crafts, this paper aims to illuminate the intricate interplay between art, culture, and economy, showcasing how Punjab’s arts and crafts are not just remnants of the past but are vibrant, living embodiments of the state’s dynamic cultural identity.